Investigating University Students’ Satisfaction with on-Campus Cafeteria Services: An Empirical Study in Perspective of Private University - Osman, Abu Rashed; Hossain, Tazkia; Sarkar, James Bakul (Asian Journal of Empirical Research, 2018)
The objective of the study is to investigate the relationship between food quality, food variety, price fairness, ambience, staff and student satisfaction with cafeteria food services. Respondents were current students of five private universities in Dhaka City of Bangladesh and data were accumulated through the convenience sampling method for reaching the objective of the study. A total number of 267 valid questionnaires were used for statistical analysis. Multiple regression, ANOVA, and T-test were used for data analysis. The results show that attributes such as food quality, ambience and staffs have a significant impact on students’ satisfaction with the cafeteria services but the highest correlation is observed between food quality and student satisfaction followed by ambience, staff, and price fairness, respectively. Management in student food services can utilize these results to ensure student satisfaction effectively. This study contributes to existing literature by assessing student satisfaction based on five dimensions of cafeteria food services which is a rare effort in Bangladesh private university perspective.